LEARNING MEDIA GRAPHICAL USER INTERFACE (GUI) BASED NUMBER BASE CONVERSION CALCULATOR - Srianto Srianto; Helmi Wibowo; Langgeng Asmoro (Sean Institute, 2023)
An understanding of the number base is needed to better understand computer work systems, one of which is the microprocessor contained in the APILL microcontroller control system. This study aims to determine the learning media for number base conversion calculators based on graphical user interface (GUI). In this study, the research location will be used in the development of number base conversion calculator learning media based on a graphical user interface at the Road Transportation Safety Polytechnic and will be tested at Wahidin Vocational School, Cirebon City. The research method used in this study uses Research and Development (R&D) research. The results of this study state that the calculator which includes 12 number base conversions is made using the Graphical User Interface (GUI) programming in the Matlab program with concise algorithms and script code and a user friendly display. And the results of conversions carried out by students manually, with the help of scientific calculators and number base conversion calculators are very significant, namely each of them gets an average value of 28.33 for manual, 48.33 with the help of a scientific calculator and 91.67 with a calculator number base conversion.